Recent Advances in Photocatalytic Decarboxylative Coupling Reactions in Medicinal Chemistry - McMurray, Lindsay; McGuire, Thomas M.; Howells, Rachel L. (Synthesis, 2020)
This review covers recent advances in decarboxylative photocatalysis applicable to the medicinal chemist. The review is not intended to be exhaustive, but instead is focussed on transformations that could be useful in the synthesis of drug-like compounds in order to highlight the utility of this methodology in the development of new pharmaceutical candidates.1 Introduction2 C–C Bond Formation3 C–N and C–O Bond Formation4 Fluorination and Trifluoromethylation5 Hydrodecarboxylation6 Protein Functionalisation7 Conclusion
Keywords: decarboxylation; photocatalysis; photoredox; medicinal chemistry; late-stage functionalisation; drug discovery